Amorphous calcium phosphate reinforced alginate-dialdehyde-gelatin (ADA-GEL) bioink for biofabrication of bone tissue scaffolds - Indurkar, Abhishek; Heid, Susanne; Bauer, Julian; Rubenis, Kristaps; Friedrich, Oliver; Locs, Janis; Boccaccini, Aldo R. (Carbohydrate Polymer Technologies and Applications, 2025)
The aim of this work was to develop a nanocomposite bioink closely resembling the nanostructure of bone incorporating amorphous calcium phosphate (ACP) as an inorganic counterpart, specifically, citrate stabilized ACP (ACP_CIT) and non-stabilized ACP (ACP_ACE) in an organic hydrogel matrix consisted of alginate dialdehyde-gelatin (ADA-GEL). The hydrogel's physical properties were evaluated, confirming the reinforcement effect of ACP. The frequency sweep analysis showed that G' and G" of ADA-GEL were 99 ± 9 Pa and 9 ± 1 Pa, respectively. By the addition of ACP_ACE, G' and G" increased. Overall, the viscoelastic and mechanical properties of ADA-GEL hydrogel were enhanced by ACP. ACP_CIT was more effective than ACP_ACE. Further, printing parameters were optimized. The bioink was formulated by embedding MC3T3-E1 cells in ADA-GEL and ACP-reinforced ADA-GEL hydrogels, followed by fabricating scaffolds at optimized printing parameters (pressure: 65 kPa, speed: 5 mm/s). Crosslinking was performed by immersing constructs in CaCl2 and microbial transglutaminase solution. Post-printing analysis was performed using the printability index and average pore area analysis. The lowest structural stability was observed in ADA-GEL constructs. The highest structural stability was noted in ADA-GEL-ACP_CIT constructs. Epifluorescence and two-photon microscopy of Rhodamine/Phalloidin stained constructs confirmed the cytocompatibility of the bioinks.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Alginate dialdehyde-gelatin bioink; Bioprinting; Bone tissue engineering; Citrate stabilized amorphous calcium phosphate; Nanocomposite bioink